2016
DOI: 10.1177/0954409716631786
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the effect of temperature-dependent stiffness of rail pads on vehicle-track coupled vibrations

Abstract: To consider the rail pads of thermoplastic polyurethane elastomer (TPE), chloroprene rubber (CR), and ethylene propylene diene monomer (EPDM) that are usually used in the Chinese subway as test subjects, their static stiffness at temperatures of À40 C to 70 C was measured by a universal testing machine equipped with a temperature control box. Then, the influence of the temperature-dependent stiffness of the rail pads on the vertical vehicle-track coupled vibrations was investigated with application of a vehicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…In general, the static stiffnesses of all three common types of rail pad are considerably sensitive to temperatures below 20°C, with chloroprene rubber (CR) rail pads being the most sensitive. Above 20°C, their static stiffnesses increase slightly with temperature; however, low-temperature (−40 to 70°C) effects on rail pad stiffness are more significant than higher temperature effects (20-70°C) (Wei et al, 2016).…”
Section: Effect Of Temperature On Elastic Padsmentioning
confidence: 98%
See 2 more Smart Citations
“…In general, the static stiffnesses of all three common types of rail pad are considerably sensitive to temperatures below 20°C, with chloroprene rubber (CR) rail pads being the most sensitive. Above 20°C, their static stiffnesses increase slightly with temperature; however, low-temperature (−40 to 70°C) effects on rail pad stiffness are more significant than higher temperature effects (20-70°C) (Wei et al, 2016).…”
Section: Effect Of Temperature On Elastic Padsmentioning
confidence: 98%
“…The elasticity of the rail pad is affected by extremely cold conditions that increase the track stiffness. Rail pads can become over-elastic in the summer, which causes track stiffness differentials (Wei et al, 2016). 3.…”
Section: Extreme Temperature Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the obtained results, it was concluded that the stiffness of railpads and, therefore, dynamic behavior of railway track vary between hot and cold days. A nonlinear behavior was observed in [9] for three different railpad materials tested at temperatures between −40°C to 70°C. The stiffness was shown to be more significantly sensitive to temperature variation below 10°C.…”
Section: Introductionmentioning
confidence: 99%
“…To address this issue, vibration mitigation measures can be implemented at the vibration source (Costa et al, 2012;Thompson et al, 2015;Vogiatzis and Kouroussis, 2015), on the propagation path (Coulier et al, 2013;Dijckmans et al, 2015), or at the receivers where vibration problems occur (Talbot and Hunt, 2003), among which source mitigation is believed to be the most cost-effective measure (Hemsworth, 2000). The source mitigation measures also include a variety of strategies: continuous welded rail (Eum et al, 2003); railpads (Wei et al, 2016(Wei et al, , 2017; special trackforms such as floating slab track (FST) (Lei and Jiang, 2014;Vogiatzis and Kouroussis, 2015;Dere, 2016) and ladder track (Xia et al, 2010); ballast mats (Auersch, 2006;Costa et al, 2012); and so on.…”
Section: Introductionmentioning
confidence: 99%